Extraction of differences in deformation behavior of golf-club shafts with different kick points - Okazaki, K.; Tsujiuchi, N.; Ito, A.; Ito, K.; Ueda, M. (Sports Engineering, 2023)
Playing golf with an appropriate club is essential to execute drives correctly and achieve low scores. Studies have been conducted on the choice of golf clubs for improved performance. A well-chosen club not only improves the shot but also the perceived "feel." However, no studies have investigated the effects of changes in the physical properties of the club on the feel yet. Therefore, this study aimed to determine the factors that influence the feel when golfers swing shafts with different kick points. A golf club was modeled using a simulation model consisting of Euler-Bernoulli beams to evaluate the deformation behavior of the shaft. Furthermore, we performed a motion capture experiment to measure the grip movement of golf-club shafts with different kick points to calculate the inertial force generated at each node. We input these force values into the simulation model to evaluate the deformation behavior of the shaft. The deformation behavior was employed as an observation matrix, and singular value decomposition was applied to evaluate the main deformation behavior in comparison with the experimental results. The deformation behavior of the shaft comprised two major deformation types, and we compared the main behaviors for different kick points. The results reveal that the angle and amplitude of the main deformation behavior changed with the changed in kick point. Finally, we also identified commonalities in golfers who preferred high-kick-point shafts.